People with weight‐related long‐term conditions want support from GPs: A qualitative interview study. Issue 5 (4th June 2021) - Talbot, Amelia; Salinas, Maria; Albury, Charlotte; Ziebland, Sue
Summary: Two‐thirds of UK adults do not have an up‐to‐date weight record in primary care. Some studies suggest that doctors do not raise the topic of weight management for fear of causing embarrassment or offence, or are doubtful whether people will make changes. However, for people with weight‐related long‐term conditions, conversations with general practitioners (GPs) can be crucial. Our study explores how people with long‐term conditions associated with overweight recall and interpret conversations about weight in British primary care. An experienced qualitative researcher interviewed 41 people aged <42  years with long‐term conditions associated with overweight. A maximum variation sample was sought, and transcribed interviews were analysed thematically. We revealed that patients with weight‐related long‐term conditions have different experiences and expectations about the role of GPs in supporting weight management. If a GP did not raise weight management in the context of the long‐term condition patients formed the impression that their overweight was not seen as "doctorable" that is, as an appropriate topic for the consultation, rather than a personal or "lifestyle" concern. This was explained in multiple ways, which are captured in two themes; perceiving weight as "doctorable"; and weight doctoring in primary care. The findings highlight the need for increased attention on weight‐related long‐term conditions in primary care. Interventions from GPs would be welcome if conducted in a sensitive, non‐judgmental manner and based on sound evidence about what works.